Denitrification and Potential Nitrous Oxide and Carbon Dioxide Production in Brownfield Wetland Soils. Issue 5 (1st September 2013) - Palta, Monica M.; Ehrenfeld, Joan G.; Groffman, Peter M.
Abstract : Brownfields, previously developed sites that are derelict, vacant, or underused, are ubiquitous in urban areas. Wetlands on brownfields often retain rain and stormwater longer than the surrounding landscape because they are low‐lying; this increases the possibility for these areas to process waterborne contaminants from the urban environment. In the northeastern United States, atmospheric deposition of nitrate (NO3 − ) is high. Denitrification, a microbial process common in wetlands, is a means of removing excess NO3 − . Nitrogen gas is the desired end product of denitrification, but incomplete denitrification results in the production of N2 O, a greenhouse gas. The goal of this study was to investigate the potential of brownfield wetlands to serve as sinks for inorganic nitrogen and sources of greenhouse gases. We examined limitations to denitrification and N2 O production in brownfield wetland soils in New Jersey. Soil C:N ratios were high (18–40) and intact core denitrification (−0.78 to 11.6 μg N2 O–N kg dry soil −1 d −1 ) and N mineralization (0.11–2.97 mg N kg dry soil −1 d −1 ) were low for all sites. However, soil NO3 − increased during dry periods. Nitrate additions to soil slurries increased denitrification rates, whereas labile C additions did not, indicating that soil denitrifiers were nitrogen limited. Incubations indicated that the end product of denitrification was primarily N2 O and not N2 . These results indicate that brownfield wetlands can develop significant denitrification capacity, potentially causing NO3 − limitation. They might be significant sinks for atmospheric NO3 − but may also become a significant source of N2 O if NO3 − deposition were to increase.